Tendence vývoje cestovního ruchu ve dvacátém a na počátku 21. století - Lacina, Karel (Univerzita Pardubice, 2010)
Tourism industry represents a significant economic, social and cultural phenomenum with global, cotinental,national and regional impacts.It represents one of the human activities which have deep historical routs.Contemporary development of the human civilization is characterized – among others – by the tourism activities rapid development typically de facto for all continents. The article is oriented both to the clarification of tourism industry development predominantly in the last 25 years and the the explanation of its regional consequences.
Keywords: tourism industry; U. N. World Tourism Organization; Tourism Viusion 2020; regional development; contemporary trends in tourism industry